Nanostructure and photovoltaic potential of plasmonic nanofibrous active layers - Schofield, RM; Maciejewska, BM; Elmestekawy, KA; Woolley, JM; Tebbutt, GT; Danaie, M; Allen, CS; Herz, LM; Assender, HE; Grobert, N (Wiley, 2024)
Nanofibrous active layers offer hierarchical control over molecular structure, and the size and distribution of electron donor:acceptor domains, beyond conventional organic photovoltaic architectures. This structure is created by forming donor pathways via electrospinning nanofibers of semiconducting polymer, then infiltrating with an electron acceptor. Electrospinning induces chain and crystallite alignment, resulting in enhanced light-harvesting and charge transport. Here, the charge transport capabilities are predicted, and charge separation and dynamics are evaluated in these active layers, to assess their photovoltaic potential. Through X-ray and electron diffraction, the fiber nanostructure is elucidated, with uniaxial elongation of the electrospinning jet aligning the polymer backbones within crystallites orthogonal to the fiber axis, and amorphous chains parallel. It is revealed that this structure forms when anisotropic crystallites, pre-assembled in solution, become oriented along the fiber– a configuration with high charge transport potential. Competitive dissociation of excitons formed in the photoactive nanofibers is recorded, with 95%+ photoluminescence quenching upon electron acceptor introduction. Transient absorption studies reveal that silver nanoparticle addition to the fibers improves charge generation and/or lifetimes. 1 ns post-excitation, the plasmonic architecture contains 45% more polarons, per exciton formed, than the bulk heterojunction. Therefore, enhanced exciton populations may be successfully translated into additional charge carriers.